Can Covered Bonds Resuscitate Residential Mortgage Finance in the United States? - Surti, Jay (IMF Working Papers; Working Paper ;, 2010)
This paper considers the case for mortgage covered bonds as an alternative to the originate-to-distribute mortgage funding model. It argues that the economic incentives provided to market participants under the covered bonds model are less susceptible to moral hazard even while retaining the key benefits of securitization such as capital market funding and flexibility in risk allocation. Notwithstanding these advantages, however, limited market size and the greater pro-cyclicality of mortgage loan quality in the United States - potentially reflecting borrower incentives under the personal bankruptcy framework - impose limits on the benefits ensuing from this model. The analysis underscores the need for a comprehensive legal-regulatory framework to underpin market development and discusses a number of ways in which the current draft legislation may be further strengthened. A potential strategy to hasten market development within the current institutional framework is identified.